(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Metronidazole is a synthetic nitroimidazole. It acts by disruption of DNA and inhibition of nucleic acid synthesis. Hypersensitivity reactions, including urticaria, pruritus, erythematous rash, and flushing have been reported; however, the frequency of reactions is not known. This is a case report of 7 year old female Child patient who was admitted in paediatric ward in King George Hospital, Visakhapatnam with a chief complaint of fever with vomiting and loose stools since 7 days. On the 2nd day of her treatment, she developed rashes and facial flushing associated with redness of face. Metronidazole was stopped after 3 days of appearance of these complaints so we suspect that it is a condition of metronidazole induced rash. Physician must suspect if such reactions occur during the treatment with metronidazole and must cautiously evaluate such drug-associated rashes.